The Example of Prophet Ayyub's Patience in Tafsir Al-Misbah - Elfa Virni Yuniafirta; Akhmad Sulthoni; Akhmadiyah Saputra (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2025)
This article discusses the exemplary character of Prophet Ayyub in facing severe trials in the form of illness, the loss of wealth, children, and social standing, as well as how the values of patience and steadfast faith reflected in his story are interpreted in Tafsir al-Mishbah by M. Quraish Shihab. The focus of this study is to explore the spiritual meanings and social relevance of the story of Prophet Ayyub through a thematic (maudhu‘i) tafsir approach using descriptive–analytical methods. The research is conducted through a literature study of relevant Qur’anic verses, particularly those in Surah Ṣād (38): 41–44 and Surah al-Anbiya’ (21): 83–84. The findings show that Quraish Shihab, through his tahlili and adabi-ijtima‘i approach, emphasizes that the patience of Prophet Ayyub is not mere passive endurance but an active and sincere submission to the will of Allah SWT. These values are highly relevant to modern life, which is filled with psychological pressures and social challenges. Through contextual and communicative explanations, this tafsir provides readers with deep insights into the meaning of life’s trials and the importance of spirituality. The study concludes that the story of Prophet Ayyub, when understood thematically through a contextual interpretation, can serve as a moral foundation and spiritual inspiration in contemporary life. The research contributes theoretically by enriching thematic tafsir studies, particularly in understanding the values of patience and steadfast faith from an adabi-ijtima‘i perspective. Practically, it offers a spiritual framework for modern society in facing life pressures—presenting patience not as passive acceptance but as a positive energy that fosters moral resilience, optimism, and closeness to God. The study reaffirms that the story of Prophet Ayyub, when approached thematically through contextual exegesis, can provide moral grounding and spiritual inspiration for contemporary living.